Urban green space in Kuching City / Muhammad Ikhwan Izzudin Weini - Weini, Muhammad Ikhwan Izzudin (2020)
The urbanization is not only focused on physical development such as the building itself, but it should come along with the urban public space that is injected with greenery that is known as urban green space. However, establishing the urban green space area is not the priority in the urbanization process especially by the private developer, this is because developers are more interested in the high investment development that give more benefits to them. As a result, most of the urban development nowadays is lacking in establishing urban green space areas that affect the nature of the urban population lifestyle. Thus, this research aims to promote the establishment of the urban green space among private developers in Kuching city. This research adopted a survey using the questionnaire were focusing on Kuching developers with more than 50 questionnaires are distributed. The result of the research is highlighting the strategies to promote the establishment of urban green space in urban development among private developers. The strategies are include the public in the decision making, recognition and awards, mandatory implementation, government incentives, and awareness workshop. The outcome of this research could help to open up the green space issued in the development by seeking the solution for arising issues faced by the developers.